Transesterification of Waste Cooking Oil Using K/Si/Fe3O4 Magnetic Composite as a Solid Catalyst - Rehan, Zainol Abidin; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim (2015)
Biodiesel has becoming brighter year by year (Boey et al.,2010). In this work, transesterification of waste cooking oil to methyl ester is being studied with the aid of K/Si/Fe₃O₄ as a solid magnetic composite catalyst. This catalyst was formed by using boiler ash and rice husk ash which is waste source. By using heterogeneous catalyst, some environmental problem cam be avoided since the catalyst can be reuse and the final product is easy to separate. The objective of this study is to synthesize and characterize the catalyst and to utilized K/Si/Fe₃O₄ and reaction duration. K/Si/Fe₃O₄ was prepared by impregnation method and calcined at 500° C for 2 hours and the catalyst was tested by Hammett indicator for its basicity. The catalyst was characterized by FTIR, BET, TGA, XRD and XRF.